Evaluasi Kualitas REST API dan Aplikasi Web E-OBE Menggunakan Pengujian Black-Box Otomatis dan Pengujian Basis Path - Abdul Azis Naufal Farizqi Naufal Farizqi; Made Hanindia Prami Swari; I Gede Susrama Mas Diyasa (Universitas Kristen Wira Wacana Sumba, 2026)
The rapid development of web-based and mobile applications in educational environments requires software testing methods that can ensure system quality, reliability, and security. The Electronic Outcome Based Education (E-OBE) application is designed to support the implementation of Outcome Based Education (OBE) through curriculum management, learning evaluation, and learning outcome assessment. This study aims to evaluate the quality of the E-OBE application based on REST API and CodeIgniter using a combination of Black Box Testing and White Box Testing approaches. Black Box Testing was conducted automatically using EvoMaster to assess REST API functionality, while White Box Testing employed the Basis Path technique to analyze program logic complexity through Cyclomatic Complexity calculations. The Black Box Testing results showed that EvoMaster generated 49 HTTP Calls and identified 27 defects, consisting of 22 API response mismatches with the documented schema, 4 HTTP 500 (Server Error) issues, and 1 authentication issue. Meanwhile, the White Box Testing results indicated that the Cyclomatic Complexity values of all tested controllers ranged from 1 to 4, which falls into the simple procedure category with a low-risk level. The findings demonstrate that the internal structure of the E-OBE application has been developed effectively; however, improvements are still required in input validation, API documentation consistency, and error handling mechanisms to enhance the overall quality of the application.